Differential effects of cow dung and its biochar on Populus euphratica soil phosphorus effectiveness, bacterial community diversity and functional genes for phosphorus conversion - Fan, Yuxian; Lv, Guanghui; Chen, Yudong; Chang, Yaling; Li, Zhoukang (Frontiers in Plant Science, 2023)
Introduction Continuous monoculture leading to soil nutrient depletion may cause a decline in plantation productivity. Cow dung is typically used as a cheap renewable resource to improve soil nutrient status. In this study, our purpose was to compare the effects of different cow dung return methods (direct return and carbonization return) on soil microbial communities and phosphorus availability in the root zone (rhizosphere soil and non-rhizosphere soil) of P.euphratica seedlings in forest gardens and to explore possible chemical and microbial mechanisms. Methods Field experiments were conducted. Two-year-old P.euphratica seedlings were planted in the soil together with 7.5 t hm-2 of cow dung and biochar made from the same amount of cow dung. Results Our findings indicated that the available phosphorus content in soil subjected to biochar treatment was considerably greater than that directly treated with cow dung, leading to an increase in the phosphorus level of both aboveground and underground components of P.euphratica seedlings. The content of Olsen-P in rhizosphere and non-rhizosphere soil increased by 134% and 110%, respectively.This was primarily a result of the direct and indirect impact of biochar on soil characteristics. Biochar increased the biodiversity of rhizosphere and non-rhizosphere soil bacteria compared with the direct return of cow dung. The Shannon diversity index of carbonized cow manure returning to field is 1.11 times and 1.10 times of that of direct cow manure returning to field and control, and the Chao1 diversity index is 1.20 times and 1.15 times of that of direct cow manure returning to field and control.Compared to the direct addition of cow dung, the addition of biochar increased the copy number of the phosphorus functional genes phoC and pqqc in the rhizosphere soil. In the biochar treatment, the abundance of the phosphate-solubilizing bacteria Sphingomonas and Lactobacillus was significantly higher than that in the other treatments, it is relative abundance was 4.83% and 2.62%, respectively, which indirectly improved soil phosphorus availability. Discussion The results indicated that different cow dung return methods may exert different effects on phosphorus availability in rhizosphere and non-rhizosphere soils via chemical and microbial pathways. These findings indicated that, compared to the direct return of cow dung, biochar return may exert a more significant impact on the availability of phosphorus in both rhizosphere and non-rhizosphere soils, as well as on the growth of P.euphratica seedlings and the microbial community.